Highlights in endocytosis of nanostructured systems - Voltan, Aline R.; Alarcon, Kaila M. [UNESP]; Fusco-Almeida, Ana M. [UNESP]; Soares, Christiane P. [UNESP]; Mendes-Giannini, Maria J.S. [UNESP]; Chorilli, Marlus [UNESP] (Bentham Science Publishers, 2017)
The focus of this review is the cellular internalisation mechanism of nanostructured systems (NSs) and their endosomal escape for targeted drug delivery. Endocytosis is a cellular process of internalisation of different molecules and foreign microorganisms. It is currently being studied for drug delivery through nanostructured systems. The most commonly studied routes of cellular uptake are phagocytosis, macro-pinocytosis, clathrin-mediated endocytosis, caveolin-mediated endocytosis, and clathrin and caveolin-independent endocytosis. The mechanism utilised by NSs for cellular entry depends on factors such as cell type and its physicochemical properties. Currently, with the development of drugs-loaded onto NSs, it has been possible to increase the therapeutic index against few diseases. The NSs can deliver the active drug at locations that conventional drugs cannot, thereby minimising unwanted side effects. On cellular entry of NSs, there is a possibility of an endosomal escape of the contents into the cytoplasm, a mechanism that can be exploited so that NSs can migrate intra-cellularly and deliver the drug to the target of interest. Designing endolysosomal escape strategy is not an easy task, but it is critical for the optimal pharmacological action on the target tissue. The cellular uptake of drugs is a very important factor in therapy. Although NSs have emerged as effective drug delivery vehicle for treatment of diseases, it is crucial to understand the mechanism of NSs endocytosis.
Keywords: Drug delivery; Endocytosis; Escape pathway endolysosomal; Nanostructured systems; Phagocytosis